Defense Mechanism Functioning in Patients With Breast Cancer: Using the Defense Mechanism Rating Scale - Saab, Marwa; Hartmann, Matias; Han, Xue (Frontiers in Psychology, 2021)
Background: Breast cancer is of the highest incidence rates in Lebanon. Previous studies had focused scarcely on breast cancer patients’ or survivors’ unconscious protective shield against cancer, while only some studies had focused on the relationship between defense mechanisms and high adaptation with the disease process and progress. Therefore, this study aimed to investigate breast cancer inpatients’ reaction towards the disease by measuring defense mechanisms in the Lebanon context. Methods: Seventy breast cancer inpatients were recruited randomly from six hospitals. Their defense mechanisms were measured using the Defense Mechanism Rating Scale. Moreover, the Relationship Anecdote Paradigm (RAP) were used with three recent life vignettes of initial diagnosis, family, daily life. Data were analyzed using repeated measure ANOVA, Wilcoxon rank sum test, and Spearman rank. Results: Stage two breast cancer patients used more high adaptive defense levels than stage four breast cancer patients who used more minor image distorting defense levels. Moreover, stage two breast cancer patients used more self-observation and undoing, while stage four breast cancer patients used more devaluation. Conclusions: The severity of BC, the carrier's age, and the social status may lead to higher use of defense mechanisms, at the level of the individual defense and the hierarchal or the tripartite levels.